2011
DOI: 10.1245/s10434-011-2109-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Sentinel Lymph Node Biopsy Using Methylene Blue Dye in Clinically Node-Negative Papillary Thyroid Carcinoma

Abstract: SLNB using methylene blue in papillary thyroid carcinoma is a safe and technically feasible procedure. However, it is of limited use in the management of clinically node-negative papillary thyroid carcinoma because of low sensitivity and a high false-negative rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 26 publications
1
23
0
1
Order By: Relevance
“…In 2012, Ji et al reported a high false-negative rate (35.1%) and low sensitivity (64.9%) with the use of methylene blue for PTC SLNB [58]. This study evaluated 114 consecutive patients with cN0 PTC, and the authors concluded that use of methylene blue for SLNB in clinically N0 PTC patients was of limited utility [58].…”
Section: Patterns Of Lymph Node Metastasismentioning
confidence: 96%
See 1 more Smart Citation
“…In 2012, Ji et al reported a high false-negative rate (35.1%) and low sensitivity (64.9%) with the use of methylene blue for PTC SLNB [58]. This study evaluated 114 consecutive patients with cN0 PTC, and the authors concluded that use of methylene blue for SLNB in clinically N0 PTC patients was of limited utility [58].…”
Section: Patterns Of Lymph Node Metastasismentioning
confidence: 96%
“…However, false-negatives may especially occur when relying on intraoperative frozen section diagnosis, and when evaluated by pathologists inexperienced in thyroid cancer histopathology [55,60]. In 2012, Ji et al reported a high false-negative rate (35.1%) and low sensitivity (64.9%) with the use of methylene blue for PTC SLNB [58]. This study evaluated 114 consecutive patients with cN0 PTC, and the authors concluded that use of methylene blue for SLNB in clinically N0 PTC patients was of limited utility [58].…”
Section: Patterns Of Lymph Node Metastasismentioning
confidence: 99%
“…38 Preoperative diagnosis was DTC in 4 studies 20,28,29,38 and PTC in 21 studies. [13][14][15][16][17][18][19]21,22,[24][25][26][27][30][31][32][33][34][35][36][37] In 2006, Abdalla 23 studied 30 patients with a preoperative diagnosis of benign thyroid nodule. The histological diagnosis of PTC ranged between a minimum of 8 patients 22,29 and a maximum of 153 patients.…”
Section: Vital Dye Techniquementioning
confidence: 99%
“…The histological diagnosis of PTC ranged between a minimum of 8 patients 22,29 and a maximum of 153 patients. 24 The authors used different vital dyes, in particular isosulfan blue in 7 studies, [13][14][15]18,23,29,31 methylene blue in 14 studies, 16,20,21,[25][26][27][28][30][31][32][33][34][35][36]38 and Patent Blue in 5 studies. 17,19,22,24,37 Injected volume ranged between 0.1 mL 13,14,16,19,22,23,28,29,36,37 and 2 mL.…”
Section: Vital Dye Techniquementioning
confidence: 99%
See 1 more Smart Citation